A French meat tax : an effective climate mitigation policy? - Dalhberg, Sanna (SLU/Dept. of Economics, 2017)
Since the agricultural sector is responsible for 14.5% of global greenhouse gas emissions, the mitigation potential of this sector might play a crucial role to reach the international agreed temperature target. In this study, we therefore investigated the effect of internalise the environmental effect of meat consumption in France, by implementing a Pigouvian tax levied on consumers to reduce greenhouse gas emissions. In the main analysis, we adopted a tax rate of €0.87 per kg beef, €0.21 per kg pork and €0.15 per kg poultry in the main analysis, corresponding to an increase between 4-8% of the initial price per kg per category in 2016. The reduction in demand was conducted by estimating a non-linear almost ideal demand system for meat. The result of the own-price elasticities indicated a slightly elastic demand for the three meat categories investigated. We concluded an absolute reduction of 5 198 217 metric ton carbon dioxide equivalent per year, equal to a decrease of GHG emissions by 9% per year compared to current level.